Sports, Culture and Advertising : Identities, Commodities and the Politics of Representation. - Jackson, Steven (Routledge, 2004)
Sport has a close relationship with advertising, both where advertisers sponsor sports, as well as where sport and 'fitness' lends its perceived positive imagery to a wide range of consumer goods. Sport, Culture & Advertising explores the themes of.